2017
DOI: 10.18203/2394-6040.ijcmph20173192
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the literature on survey questionnaires to assess self-medication practices

Abstract: Self-medication is of great public health importance as it often bypasses regulatory mechanisms to assure quality of health care. Nevertheless there are no established standards on how to assess self-medication. We therefore intended to systematically retrieve questionnaires and survey tools used to capture self-medication, with the aim to identify the scope of information investigated in this context and commonalities between the tools. We conducted a systematic review of the literature on questionnaires used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
81
0
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(97 citation statements)
references
References 11 publications
5
81
0
11
Order By: Relevance
“…Self medication is a very common practice today. 16 It we use any medicine which is already available in our home or if we are using medicines which has been prescribed for any other person then also it is self medication. 17 In present study 88.15% students have used analgesics as self medication out of which 85.81% were males and 90.41% were females (p >0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Self medication is a very common practice today. 16 It we use any medicine which is already available in our home or if we are using medicines which has been prescribed for any other person then also it is self medication. 17 In present study 88.15% students have used analgesics as self medication out of which 85.81% were males and 90.41% were females (p >0.05).…”
Section: Discussionmentioning
confidence: 99%
“…1 Previous studies also have reported that the prevalence of self medication among medical student of Bangladesh was high as 65.2% as well as, 88.18% in Karnataka, India, 76% in Karachi.3 Main sources of self medication are relatives, friends, pharmacists who not only provide medicines but also the information about usage of drug. 5 Media exposure and pharmaceuticals advertisement pose a larger threat in providing self medication practice. 6 Several factors like costly consultation, lack of access to health care, time constraint, lack of trust on physician, inadequate implementation of drug laws have been shown to indulge this practices.…”
Section: Worldmentioning
confidence: 99%
“…6 Several factors like costly consultation, lack of access to health care, time constraint, lack of trust on physician, inadequate implementation of drug laws have been shown to indulge this practices. 5,7 Benefits of self medication is precised as convenient, cost effective, product safety when used as recommended in the instructions and self reliant to the recipient in preventing or relieving 1 minor symptoms or condition 7 , 8 on the other hand several studies have indicated that inappropriate self medication results in adverse drug reactions, misdiagnosis of disease, drug interactions, antibiotic resistance, treatment failure, unintentional and intentional poisonings, drug abuse and misuse, increased morbidity, drug market disruption, financial loss and wastage of healthcare resources. 3-5.7,9 Because of its favourable and unfavourable consequences, self medication has an substantial impact in healthcare sector.…”
Section: Worldmentioning
confidence: 99%
“…Prevalence of self-medication in India varies widely from 27.6% to 81.5%. 11 Pharmacists can play a pivotal role in both ADE reporting and PV activities. 12 Pharmacists are more likely to detect adverse drug events (ADEs) than are other healthcare professionals, either in the hospital or community setting.…”
Section: Introductionmentioning
confidence: 99%